2013
DOI: 10.1007/s00125-013-3101-z
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin-interacting protein is required for endothelial NLRP3 inflammasome activation and cell death in a rat model of high-fat diet

Abstract: Aims/hypothesis Obesity and hypertension, known pro-inflammatory states, are identified determinants for increased retinal microvascular abnormalities. However, the molecular link between inflammation and microvascular degeneration remains elusive. Thioredoxin-interacting protein (TXNIP) is recognised as an activator of the NOD-like receptor pyrin domain containing-3 (NLRP3) inflammasome. This study aims to examine TXNIP expression and elucidate its role in endothelial inflammasome activation and retinal lesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
127
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(141 citation statements)
references
References 50 publications
12
127
0
Order By: Relevance
“…It is consisted of studies from others and our previous work [7,30,31]. The maturation of IL-1b is dependent on NLRP3 inflammasome assembling and the following activation [9,32,33]. However, little attention has been directed toward identifying the role of NLRP3 inflammasome in the PVN of saltsensitive hypertensive rats.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is consisted of studies from others and our previous work [7,30,31]. The maturation of IL-1b is dependent on NLRP3 inflammasome assembling and the following activation [9,32,33]. However, little attention has been directed toward identifying the role of NLRP3 inflammasome in the PVN of saltsensitive hypertensive rats.…”
Section: Discussionmentioning
confidence: 97%
“…The maturation of IL-1b is dependent on NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome assembling and the following activation [9], but at present, there are no reports on regulation of NLRP3 within the PVN.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of Nlrp3 can induce cell death via caspase-dependent mechanisms (27,34). Previous studies have shown that activation of Nlrp3 inflammasome has also been shown to induce cell death in human retinal ECs (28). Nlrp3 deficiency prevented caspase 3-mediated apoptosis by upregulating autophagy, specifically mitophagy in lungs and lung ECs during hyperoxia (56).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the NLRP3 inflammasome plays a role in the development of insulin resistance and T2D (12)(13)(14)31). However, the role of the NLRP3 inflammasome in autoimmune T1D remained to be explored.…”
Section: Discussionmentioning
confidence: 99%